Physicochemical, genomic, and phenotypic characterization of Escherichia phage BME3 - Belén Toaquiza-Vilca; Diego Quito-Avila; Pedro Maldonado-Alvarado; Omar Ruiz-Barzola; Alexis Debut; Marynes Montiel (Microbiology Spectrum)
ABSTRACT Infections caused by pathogenic Escherichia coli strains are increasing, and with the rising of antimicrobial resistance among bacterial pathogens, alternative therapeutic options are being actively explored, including phage therapy. In this research, a new bacteriophage, provisionally named BME3, with lytic activity against Escherichia coli was identified and characterized at the physicochemical, morphological, and genetic levels. BME3 was isolated from the tropical estuarine waters of Estero Salado, Guayaquil, Ecuador. Subsequently, it was purified and amplified, followed by a series of tests that included host range, stability studies, morphological characterization by transmission electron microscopy (TEM), and whole genome sequencing. The genomic analysis revealed that BME3 is closely related to members of the genus Justusliebigvirus, with a double-stranded DNA genome of 147,371 bp in length, a GC content of 37.5%, and 16 tRNA genes. In addition, BME3 lacks genes associated with lysogenesis, antibiotic resistance, or virulence. BME3 infected approximately 48% (13/27) of environmental E. coli strains. Among these, the infection rate was higher for antibiotic-resistant strains (67%) compared to intermediate and sensitive strains (33%). The phage infected E. coli and Salmonella sp. strains but did not affect Bacillus sp., Pseudomonas sp., or Vibrio sp. Moreover, BME3 was found to be stable at temperatures below 60°C, in pH ranges between 5 and 9, and was not sensitive to chloroform. TEM analysis supported the genetic sequence that assigned BME3 to the class Caudoviricetes. Phenotypic, genomic, and physicochemical characterization suggests that BME3 represents a promising option for phage therapy, with the potential to control antibiotic-resistant bacteria.IMPORTANCEAlthough metagenomics offers a wealth of information, not all microorganisms can be isolated and cultivated in the laboratory. In this study, we successfully isolated and characterized a phage belonging to the Justusliebigvirus genus. This group has been poorly studied regarding its physicochemical properties and lysis profile against antibiotic-resistant environmental bacteria. These bacteriophages have received less attention compared to well-studied models such as phage T4. The isolation and characterization of the indigenous polyvalent bacteriophage BME3, obtained from tropical estuarine waters in Ecuador, provide valuable insights into its potential applications for environmental control of Escherichia coli and for mitigating the spread of bacterial resistance.